Can ultrasound predict malignancy in patient with thyroid cold nodule? - Joko Wiyanto; Achmad Kartamihardja; Trias Nugrahadi (World Journal of Nuclear Medicine)
Thyroid nodule is one of the most common endocrine diseases in the world; it occurs in 4-7% of the general population. Depending on the method of discovery, 4-8% nodules are discovered using palpation, 10-41% with ultrasound (US), and 50% through autopsy where only 20% or less of cold thyroid nodules are caused by cancerous lesions. The aim of this study was to assess US as supporting modality for thyroid scintigraphy to predict malignancy in patient with thyroid cold nodules. In a retrospective study between 2009 and 2013, we analyzed 399 subjects with cold thyroid nodule, where 39 subjects (36 women and 3 men) presented with malignant thyroid cold nodule and 19 subjects underwent US. The US showed malignancy parameters in 8 (42.11%) subjects, while the rest of the 11 (57.89%) subject were benign. Out of all the subjects who underwent US in this study, only 8 (42.11%) subjects shown malignancy characteristics in cold thyroid nodule with  papillary thyroid cancer (PTC). That means US parameters of malignant thyroid nodule do not always show up in malignant cold thyroid nodule.